Uncovered interest parity with foreign exchange interventions under exchange rate peg and inflation targeting: The case of Ukraine - Anton Grui (Graduate Institute of International and Development Studies, 2020)
In this study, I modify the uncovered interest parity condition to account for foreign exchange interventions in the context of a small open economy. This is done in a framework of a semistructural New Keynesian model. I examine the case of Ukraine, which de facto transitioned to inflation targeting with a managed float in 2015 after a long period of pegged exchange rate. I simulate model-consistent foreign exchange interventions and use them to quantify the effectiveness of those actually observed. The proposed modification is relevant for inflation targeting regimes with foreign exchange interventions as an additional instrument and those in transition.
Keywords: E12; E17; E52; F31; 330; New Keynesian model; UIP; exchange rate; FX interventions